2015
DOI: 10.18632/oncotarget.6631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cardiac-related circulating microRNA profile in human chronic heart failure

Abstract: BackgroundDuring chronic heart failure, levels of circulating miRNAs endued with characteristics of diseased cells could be identified as biomarkers. In this study, we sought to identify cardiac-related circulating miRNAs as biomarkers of failing heart.MethodsTotal RNA of plasma and heart samples was extracted from 10 normal controls and 14 patients with chronic heart failure. Microarray was applied for miRNA profiles. Validation and organ/tissue distribution analysis was performed by qRT-PCR. In addition, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…For example, miR-660-5p was revealed to be downregulated in thyroid tissues of patients with Graves' disease, which suggested a potential involvement of miR-660-5p in the pathogenesis of this disease (36). Aberrant expression of miR-660-5p, as detected by RT-qPCR, demonstrated a relationship with the prediction or diagnosis of myocardial infarction or chronic heart failure (37,38).…”
Section: Discussionmentioning
confidence: 98%
“…For example, miR-660-5p was revealed to be downregulated in thyroid tissues of patients with Graves' disease, which suggested a potential involvement of miR-660-5p in the pathogenesis of this disease (36). Aberrant expression of miR-660-5p, as detected by RT-qPCR, demonstrated a relationship with the prediction or diagnosis of myocardial infarction or chronic heart failure (37,38).…”
Section: Discussionmentioning
confidence: 98%
“…Recent study identified that three cardiac fibroblast-derived miRNAs (miR-660-3p, miR-665, and miR-1285-3p) were found obviously elevated in heart and plasma during CHF and significantly correlated with left ventricular ejection fraction (LVEF), holding promise as potential diagnostic biomarker for CHF. These three circulating miRNAs may be used as potential biomarkers for diagnosis of CHF patients [ 67 ].…”
Section: Circulating Mirnas As a Potential Biomarker For Hf Patienmentioning
confidence: 99%
“…DJ-1 was also shown to protect the heart from ischemiareperfusion injury [142,143]. Moreover, the work of Li et al shows that miR-4639 is almost 3-fold overexpressed in chronic heart failure patients compared to the control group [144]. All this leads us to the following hypothesis (see Figure 3): "overexpression of miR-4639 in the heart downregulates DJ-1 that protects the heart from oxidative damage, which may be one of the causes leading to heart failure.…”
Section: Example 2: Hypotheses and Potentially New Insightsmentioning
confidence: 99%